Independent Assessment of Future Nuclear Power Specialist Qualifications as a Factor of Nuclear Power Plant Safety - V. A. Rudenko; N. F. Privalova (Глобальная ядерная безопасность, 2022)
The paper considers the sectoral system of professional qualifications assessment in the field of nuclear energy, its structural components, and reveals the main tasks and activities for its improvement and development. The relevance of independent assessment of qualifications of future engineering personnel specialized in nuclear power industry at the stage of completion of higher education is disclosed.